Bibliometric Analysis of Inclusive Public Services Research in Indonesia - Simanjuntak, Jeremia Gom Gom Parulian; Monim, Oktovina Hanani Kristin; Novita, Virgilia Karin; Rachman , Muthia Zahira; Yubawa, Cindy Kartini (The Center for Disability Studies and Services Brawijaya University, 2023)
To advance knowledge and improve people's lives, good research must incorporate components of recent findings. The novel knowledge and contributions that come from that research are one of the key problems in compiling research. To determine the uniqueness of the research, it is crucial to consider how frequently prior studies on a certain topic have been conducted. This bibliometric analysis uses the Google Scholar database to investigate the rise in publications about inclusive public services in Indonesia. The Mendeley, VOSviewer, and Publish or Perish tools are used in this bibliometric analysis. To determine the publication of the growth of public services in Indonesia, 1,113 articles were gathered and analyzed. The analysis's findings demonstrate that there has been extensive research on public services as they relate to individuals with disabilities, those with impairments, and ensuring accessibility. In contrast, research is still sparse on issues connected to comprehensive, inclusive public service management. Thus, it is recommended that more research be done on this under research topic.